2019
DOI: 10.3892/or.2019.7177
|View full text |Cite
|
Sign up to set email alerts
|

Bile cell‑free DNA as a novel and powerful liquid biopsy for detecting somatic variants in biliary tract cancer

Abstract: Tissue sampling of biliary tract carcinomas (BTCs) for molecular characterization is challenging. The aim of this study was to investigate the possibility of identifying individual actionable mutations derived from bile cell-free DNA (cfDNA) using targeted deep sequencing. Ten BTC patients, four with gallbladder carcinomas and six with cholangiocarcinomas, were enrolled in the present study. Using targeted deep sequencing with a panel of 150 tumor-related genes, paired bile cfDNA and tumor DNA were analyzed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 31 publications
8
47
0
1
Order By: Relevance
“…Brush cytology and forceps biopsies displayed an overall sensitivity of 77.1% for the diagnosis of suspected malignant biliary strictures when obtained by ERC(P) [ 29 ]. Our results are in line with the previous studies, which reported high sensitivity and specificity of bile cfDNA analysis in gallbladder cancer and cholangiocarcinoma [ 30 , 31 ] and showed its value as ancillary method in the diagnosis of malignant biliary strictures [ 32 ]. This is the first study reporting on the usefulness of bile as a source of liquid biopsy in PDAC.…”
Section: Discussionsupporting
confidence: 92%
“…Brush cytology and forceps biopsies displayed an overall sensitivity of 77.1% for the diagnosis of suspected malignant biliary strictures when obtained by ERC(P) [ 29 ]. Our results are in line with the previous studies, which reported high sensitivity and specificity of bile cfDNA analysis in gallbladder cancer and cholangiocarcinoma [ 30 , 31 ] and showed its value as ancillary method in the diagnosis of malignant biliary strictures [ 32 ]. This is the first study reporting on the usefulness of bile as a source of liquid biopsy in PDAC.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, a recent study demonstrated the presence of larger cfDNA fragments (1000–6000 bp) in bile—a body fluid that does not likely possess the same DNA degradation qualities of plasma. 41 Alternatively, intact larger cfDNA fragments may be missed due to the use of DNA extraction methods that are biased toward the isolation of small cfDNA fragments. It is likely that the resolution of such an experimental problem may only be achievable through a method or combination of methods that allow the complete recovery and high resolution differentiation between all cfDNA populations (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, the option to use the bile as source for DNA sequencing in BTC has been recently investigated and deserves to be mentioned, since bile is another component of liquid biopsy. A recent study by Shen et al from 10 BTC patients (including 4 cases of GBC) suggested that bile cfDNA could consist of long fragments, with a high correspondence between molecular features detected in bile and tissue sampling (129). Studies on larger cohorts of patients are needed to confirm the above results and to further assess the role of bile as source of cfDNA.…”
Section: Diagnosismentioning
confidence: 96%